Peningkatan Keterampilan Membaca Permulaan Melalui Media Gambar Berbasis Konstruktivisme pada Siswa Beresiko Lambat Belajar : Improving Early Reading Skills in Students at Risk of Slow Learning Through Constructivism-Based Image Media - Khoiriyah Khoiriyah; Rendy Roos Handoyo (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
This study aims to improve the early reading skills of students at risk of slow learning through the implementation of constructivism-based image media. The study employed the Classroom Action Research (CAR) method using the Kemmis and McTaggart model and was conducted over two cycles; each cycle comprised the stages of planning, action implementation, observation, and reflection. The subjects were two second-grade students at SD Negeri 006 Long Mesangat (2025/2026 academic year) identified as being at risk of slow learning and experiencing difficulties with early reading. Data collection involved observation and performance tests, while data analysis was conducted using both quantitative and qualitative descriptive approaches. The results indicate that the use of constructivism-based image media successfully improved the quality of the learning process and the students' early reading skills incrementally. The average reading skill score rose from 40% in the pre-cycle stage (categorised as "needs guidance") to 70% in Cycle I (categorised as "sufficient"), and further increased to 90% in Cycle II (categorised as "excellent"). This improvement occurred because the image media provided concrete, engaging, and meaningful learning experiences, thereby helping students construct an understanding of letter symbols, vowels, consonants, syllable blending, and simple word reading in accordance with constructivist principles. Thus, constructivism-based image media is effective for enhancing early reading skills among elementary school students at risk of slow learning.